Faktor-Faktor Yang Berhubungan Dengan Kejadian Anemia Pada Ibu Hamil Di Puskesmas Batua Kota Makassar Sulawesi Selatan - Jumrana Jumrana; Kasmawati Kasmawati (The Journal General Health and Pharmaceutical Sciences Research, 2023)
The aim of this research is to determine the factors associated with the incidence of anemia in pregnant women at the Batua Makassar City Health Center. The type of research used in this research is using analytical research methods with a Cross Sectional Study approach. The population of this study was all 180 pregnant women who underwent pregnancy checks in the Batua Community Health Center Working Area, Manggala District. The sampling technique used in this research is purposive sampling, namely where pregnant women who undergo pregnancy examinations who meet the inclusion criteria when conducting research are used as samples. The sample in the study was 35 pregnant women who experienced anemia during pregnancy. The data collection technique in this research is secondary data, namely data obtained from the medical records of the Batua Community Health Center, Manggala District. In the research, the instrument used was an observation sheet made by the researcher based on theory. The data analysis used is univariate analysis and bivariate analysis using SPSS. The results of the research show that based on the chi square statistical results, the Fisher Exact Test value was obtained = 0.027 < α 0.05, which shows that maternal age is a factor related to the incidence of anemia in pregnant women at the Batua Community Health Center, Manggala District, Makassar City, then based on the chi statistical results square, the Fisher Exact Test value was obtained = 0.012 < α 0.05, which indicates that pregnancy spacing is a factor related to the incidence of anemia in pregnant women at the Batua Community Health Center, Manggala District, Makassar City.